The Effect of English Capacity Building and Interest in English by Micro, Small and Medium Enterprises Managers on the Service Quality Tourist Destination in Simalungun Regency - Abdul Kadir Ritonga (BIRCU, 2022)
This research is entitled the effect of English Capacity Building and Interest in English by Micro, Small and Medium Enterprises (MSME) managers on the quality of service in tourist destinations in Simalungun Regency. The purpose of this study was to determine how much influence English Capacity Building and Interest in English have on the quality of service in tourist destinations in Simalungun Regency. The research design used observation and quantitative research and the sample in this study was non-probability sampling, namely the accidental sampling technique. The number of samples was 109 respondents from MSME managers in Parapat, Simalungun Regency. Data collection techniques through direct observation. Data analysis was carried out in a quantitative descriptive manner using SPSS with the F test and t test. The results of the study show that firstly there is a significant effect of English Capacity Building for MSME managers on service quality, secondly there is a significant influence on the English language interest of MSME managers on service quality, and thirdly there is a significant influence on English Capacity Building and MSME managers' English interest in service quality. F significance value of 0.000 is smaller than 0.05 then Ho is rejected or the proposed hypothesis is accepted and the partial t-test shows a significant effect as seen from the significance values of 0.005 and 0.003 respectively, which are smaller than 0.05. Concluded that simultaneously the independent variables have a significant effect on the dependent variable.